CONDITIONS UNDER WHICH VELOCITY-WEAKENING FRICTION ALLOWS A SELF-HEALING VERSUS A CRACKLIKE MODE OF RUPTURE - Zheng G.; Rice J.R. (My University, 1998)
Slip rupture processes on velocity-weakening faults have been found in simulations to occur by two basic modes, the expanding crack and self-healing modes. In the expanding crack mode, as the rupture zone on a fault keeps expanding, slip continues growing everywhere within the rupture. In the self-healing mode, rupture occurs as a slip pulse propagating along the fault, with cessation of slip behind the pulse, so that the slipping region occupies only a small width at the front of the expanding rupture zone. We discuss the determination of rupture mode for dynamic slip between elastic half-spaces that are uniformly prestressed at background loading level r0 b outside a perturbed zone where rupture is nucleated. The interface follows a rate and state law such that strength z-strength approaches a velocity-dependent steady-state value z-s,(V) for sustained slip at velocity V, where dz-ss(V)/dV z-pulse. Here Z'puls e is the largest value of z0 b satisfying z-o b - (,u/2c)V 0, where ,u is the shear modulus and c is the shear wave speed. Also, T = (-dz-~(V)/dV)/(,u/2c) eval- uated at V = Vdyna , which is the largest root of z-o b - (,u/2c)V = rs~(V); T = 1 at z-b = Z-pulse, and T diminishes toward 0 as z-o b is increased above z-pulse- We thus show that the rupture mode is of the self-healing pulse type in the low- stress range, when z-o b < z-pulse or when Zo b is only slightly greater than z- pulse, such that T is near unity (e.g., T > 0.6). The amplitude of slip in the pulse diminishes with propagation distance at the lowest stress levels, whereas the amplitude increases for z-o b above a certain threshold z-west, with z-arrest < z-pulse in the cases examined. When z-o b is sufficiently higher than z-pulse that T is near zero (e.g., T < 0.4 in our 2D antiplane simulations), the rupture mode is that of an enlarging shear crack. Thus rupture under low stress is in the self-healing mode and under high stress in the cracklike mode, where our present work shows how to quantify low and high. The results therefore suggest the possibility that the self-healing mode is common for large natural ruptures because the stresses on faults are simply too low to allow the cracklike mode.